Regions of Russia - Yuri Solozobov (Ksiegarnia Akademicka Publishing, 2019)
The article focuses on a possible classification and description of the real situation in the regions of Russia whose developmental trends have not been included so far in the studies about the processes the state really undergoes. The main thesis of the work boils down to stating the extraordinary diversity of the level and type of development of individual subjects of the Federation. A helpful method for describing the state of Russian regions is first and foremost the observation of changes in energy consumption for lighting purposes based on satellite images. The author divides Russia’s socio-regional body into the First Russia (cities populated by more than 500 thousand inhabitants), the Second Russia of smaller cities and towns and the Third Russia – the country’s peripheries. The conclusions of the study are not optimistic as they emphasize the extinction and underdevelopment of most of the state’s territory (representing the Third Russia) accompanied by the unnatural growth of the metropolitan areas, with Moscow and St. Petersburg at the forefront.